2002
DOI: 10.1016/s1381-1169(01)00423-x
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase heterogeneous catalytic enantioselective hydrogenation of acetophenone over cinchona-modified Pt/C

Abstract: The multiphase heterogeneous enantioselective hydrogenation of acetophenone in the presence of cinchona-modified Pt/C was investigated. The system demonstrated the feasibility of this reaction on non-activated ketones. The reaction proceeded selectively, at room temperature and atmospheric pressure, towards the formation of 1-phenylethanol, with up to 20% ee (enantiomeric excess) of either enantiomer depending on the modifier used. A mode of action of the modifier is proposed to account for the mechanism. A co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…The selectivity, kinetics, and synthetic (10,11) and environmental applications (12) of the multiphase systems have been amply studied for charcoal-supported Pt and Pd catalysts. Some mechanistic hypotheses on the mode of action of the multiphase environment have been proposed as well (7).…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity, kinetics, and synthetic (10,11) and environmental applications (12) of the multiphase systems have been amply studied for charcoal-supported Pt and Pd catalysts. Some mechanistic hypotheses on the mode of action of the multiphase environment have been proposed as well (7).…”
Section: Introductionmentioning
confidence: 99%
“…85 The idea was to employ chiral phase transfer agents derived from chincona alkaloids in place of A336, coupled with Pt/C as catalyst. A rapid screening, however, demonstrated that the pure alkaloids chincona and chinconidine were more active than the corresponding ammonium salt in promoting a degree of enantioselectivity in the reduction of acetophenone (Fig.…”
Section: Reductionmentioning
confidence: 99%
“…According to the literature, in biphasic IO/H 2 O solvent system a variety of catalytic reductions can effectively proceed under mild conditions (ca. 50°C, atmospheric pressure of hydrogen) and their selectivity can be modified [24][25][26][27]. Thus, Marques et al [24] demonstrate that hydrogenation of propiophenone on Pd/C catalyst in conventional ethanol solvent produces propylbenzene as the final product, while in the biphasic IO/H 2 O system propiophenone is almost selectively reduced to 1-phenyl-1-propanol [24].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, on Pt/C catalyst and in IO/H 2 O system, the hydrogenation of acetophenone and propiophenone proceeds towards the full reduction products, ethyl benzene and ethyl cyclohexane, respectively [25,26]. Biphasic IO/H 2 O system is also successfully used for enantioselective hydrogenation of ACT in the presence of cinchona-modified Pt/C catalyst [27]. Moreover, our preliminary catalytic data demonstrate the advantage of biphasic IO/H 2 O solvent system in hydrogenation of ACT in the presence of Ru-catalysts supported on methacrylate-styrene gel-type resin (FCN) (Scheme 2).…”
Section: Introductionmentioning
confidence: 99%